MANUAL VACUUM ASPIRATION (MVA): A SAFE AND EFFECTIVE ALTERNATIVE FOR THE SURGICAL MANAGEMENT OF EARLY PREGNANCY LOSS: MVA: In Early Pregnancy Loss - Baqai, Shehla; Waheed, Anam Akbar (Pakistan Armed Forces Medical Journal, 2016)
Objective: To assess and document safety, efficacy and patient acceptability of Manual vacuum aspiration (MVA) in the management of early pregnancy loss (EPL), performed in the treatment room setting. Study Design: Quasi-experimental, (clinical trial), Place and Duration of Study: Treatment Room, OBGYN department, PNS Shifa from Nov 2010 to 31st Mar 2013. Material and Methods: Single centre prospective study conducted at Obstetric & Gynecology department, PNS Shifa from Nov 2010 to Mar 2013. A total of 414 women with EPL consented for MVA in the treatment room under local anesthesia, out of which 400 women underwent MVA. Results: Overall MVA was 94.5% effective in treating pregnancies through 13 weeks of gestation. There were no major complications. Minor complications: retained products of conception and endometeritis were treated easily. Conclusion: MVA is safe, effective and economical alternative to conventional dilatation and curettage for the treatment of EPL. Treatment in the outpatient setting allows better post-procedure physical and emotional quality of life; avoids general anesthesia, has immense potential in primary health care setting.